Caroli's Disease: A case report - Patowary, BN; Kumar, S; Pun, A; Kafle, P; Chhetri, PK (Journal of College of Medical Sciences-Nepal, 2013)
Caroli's disease (CD) is a rare congenital abnormality characterized by dilatation of intra-hepatic bile ducts, recurrent cholangitis, formation of calculi inside these ducts with normal extra hepatic ducts and higher risk for cholangiocarcinoma. Association of this disease with congenital hepatic fibrosis is named as Caroli's syndrome. We reported 30 years old women with recurrent epigastric pain for 2 years with normal Liver function Test however involving both lobes of liver who developed cholangiocarcinoma approximately 6 months later. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 51-54 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8685